Effect of replacing fish meal by yeast hydrolysate on growth and intestinal function of juvenile Jian carp (Cyprinus carpio var. jian) - Yuan, Xiangyang; Liu, Wenbin; Jiang, Guangzhen; Dai, Yongjun; Desouky, Hesham Eed (Indian Journal of Fisheries, 2021)
This experiment was performed to investigate the effects of replacing fish meal in the diet of Cyprinus carpio var. jian (average weight 19.44Â±0.06 g) by yeast hydrolysate (YH), on growth, intestinal histology and function. Six hundred fish were assigned into five groups and fed with five isonitrogenous and isocaloric diets replacing fishmeal by 0% (G1), 1% (G2), 3% (G3), 5% (G4) and 7% (G5) YH. YH supplementation at 3% level significantly increased average body weight, daily growth index, feed intake, condition factor, speciï¬c growth rate, intestinal villi length and digestive and brush-border enzymes activity compared to the control group (p<0.05). Moreover, YH supplementation significantly increased (p<0.05) intestinal lipase, Î³-GT, Na+/K+-ATPase and AKP expression levels. Intestinal Claudin-7 and Occludin mRNA levels in fish of dietary group G5 were significantly higher (p<0.05) than that in the control group. Replacing fish meal with 3% YH increased growth performance, intestinal digestion and absorption, as well as improved intestinal villi length without triggering any negative effects on intestinal tight junction structure. Keywords: Enzyme activities, Growth, Intestinal histology, Jian carp, Tight junction structure, Yeast hydrolysate